Post Islamisme Turki Studi Praksis Politik Adalet Ve Kalkinma Partisi (AKP) - Gili Argenti (Jurnal Politikom Indonesiana, 2019)
Political Islam in Turkey is considered by several circles to be the ideal form of Islamic political praxis in a democratic system. The socio-political phenomenon becomes an antithesis regarding the labeling that Islam cannot go hand in hand with democracy. The political praxis of post Islamism represented by the Adalet Ve Kalkinma Partition (AKP) is proof that Islam is able to adapt and participate in a democratic system. Post Islamism is a new model of a political Islam group that is very aspirational with the values of openness, freedom and equality. This paper is a literature study on the political practices of AKP that take a pragmatic and non-ideological approach, so they are able to attract constituents from other communities outside their traditional groups. The post Islamism model developed by the AKP can be a reference for other political Islamic groups about how to adapt to a system of democratic systems that has become a global trend. Keyword: Political Islam, Adalet Ve Kalkinma Partisi (AKP), Post Islamism.